Sociodemographic Determinants of Physical Activity and Sport Participation among Women in the United States - Jennifer R. Pharr; Nancy L. Lough; Angela M. Terencio (MDPI AG, 2020)
Regular physical activity and sport participation have been shown to improve women's health; however, research has found that better health is associated with sport participation. Little is known about the sociodemographic determinants of physical activity among women, especially among the different subcategories of physical activity (sport, conditioning exercise, recreation, and household tasks). Because of the added health benefits associated with sport participation, the purpose of this study was to examine the sociodemographic determinants among subcategories of physically active women in the United States by analyzing Behavioral Risk Factor Surveillance System (BRFSS) data. We used data from the 2017 national BRFSS survey to conduct this secondary data analysis. Participants were asked an extensive set of questions about their physical activity. Seventy-six different activities were identified and categorized as either sport, recreation, conditioning exercise, or household tasks. Weighted descriptive statistics were performed to describe the sociodemographic determinants of the four physical activity subcategories, including age, income, education, employment, and race/ethnicity. There were significant differences in all sociodemographic variables among the four subcategories of physical activity. Women who participated in sport were more likely to be in the younger age groups; however, physical activity declined among all subcategories beyond the age of 64. Women who participated in sports were more diverse, likely to be employed, and college graduates compared to the other subcategories. Women who participated in recreational or household tasks were more likely to meet the criteria to be categorized as highly active; however, they exercised at a lower intensity. The sociodemographic characteristics of physical activity and sport participation can be used to create promotional strategies to increase physical activity and improve fitness and health among women who tend towards participation, and also to change programs to accommodate women from other sociodemographic groups.